Effek Video Online Pembelajaran Pemeriksaan Fisik Terhadap Kemampuan Mahasiswa Keperawatan Dalam Melakukan Pemeriksaan Fisik Abdomen - Fajar Agung Nugroho (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Background: Accurate physical assessment is one of the nursing interventions that must be owned by nursing students. Learning videos in education are not optimal, even though this learning media is very supportive to improve student skills.Purpose: to explore nursing students’ skill of their competency following an online video simulation and self-reflection in nursing skills practice.Method: this research used quasi-experimental design in the form of pre-test and post-test. Sixty respondents were divided into the control and treatment group. Where the control group was given a conventional method and treatment group was given an online video simulation that was made by researcher.Result: The t-test analysis resulted in a sig value. (2-tailed) of 0.000 (< 0,05). It was that there were differences in nursing skills between the control and the experiment group.Recommendation: Further research needs large sample sizes when want to measure students’ skill and researcher have to be strict when choosing research sample to control confounding variables.